A Study of Consumer Preferences towards Carbonated and Non Carbonated Drinks with Reference to Dewas city - Ubeja, Satnam Kour; Patel , Ranjana (Gyan Management Journal, 2014)
The soft-drink industry comprises companies that manufacture nonalcoholic beverages and carbonated mineral waters or concentrates and syrups for the manufacture of carbonated beverages. Soft drink products have been well accepted by consumers and gradually overtaking hot drinks as the biggest beverage sector in the world. The beverages sector in India has undergone significant transformation in the past 10 years. The carbonated and non carbonated drinks industry in India is to grow near about 55 per cent annually and would triple or four times in size by 2015. Customer preferences are more complex and even more important/or retailers today than in past. The objectives of this study to identijj, the factors affect on consumer preference towards carbonated and non carbonated drinks with respect to Dewas city. This intercept survey was conducted to study of consumer preferences towards soft drinks in Dewas City. The sample included 200 active mall shoppers. The consumer preferences were identified by a structure questionnaire and captured in 6 factors of preferences. These sales promotion mix factors Satisfaction of mental thirst, Price and availability through ambassador promotion, Relaxation and refreshment on celebration, Brand Positioning, Reliability and cleanness and Taste . The study will help the retailers and manufacturers of soft drinks to understand the underlying consumer preferences factors and which factor mostly like by the customers of Dewas city and help them to craft their marketing strategies. Profiling customers by their choice of preferences provide more meaningful ways to identijj, and understand various customer segments and marketing strategies.